Building from the ground up: Reconstructing visions of community in Cambridge Bay, Nunavut - Griebel, Brendan (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2013)
The Inuit qalgiq, or gathering house, once served as a forum for bringing communities together through acts of storytelling, drum dancing, shamanism, and the intergenerational transfer of knowledge. While the specific traditions associated with these structures have varied over time and space, they have remained of central importance to the affirmation of group identity and communal decision-making. In 2008, the excavation of an early Thule qalgiq near the Nunavut hamlet of Cambridge Bay provided a team of local participants and University of Toronto archaeologists with an opportunity to interpret the social position of the qalgiq in the context of a contemporary Inuit population currently struggling with issues of collective identity. This article presents a project originally designed to reconstruct a qalgiq as a museum exhibit with a structure drawn primarily from archaeological findings. By embedding the project in local understandings of history as a source for community wellness and revival, however, a different course was taken. While combining archaeological blueprints with contemporary realities and beliefs, the qalgiq was ultimately re-imagined as a venue in which ideas about community, both past and present, can be voiced.